HUBUNGAN PERAN SERTA ORANG TUA DENGAN DAMPAK HOSPITALISASI PADA ANAK USIA PRASEKOLAH DI RUANGAN SANTA THERESIA RUMAH SAKIT SANTA ELISABETH MEDAN 2015 - Samfriati Sinurat (Elisabeth Health Jurnal, 2016)
The hospitalization is a full of stress experience both for children and for parents. The intervention of parent is needed to minimize the impact of hospitalization. Goal: this study aimed to analyze the relationship between the intervention of the parents and the impact of hospitalization on children of preschool-age who were treated in kid room of Saint Theresa Saint Elizabeth Hospital Medan. Method:The method used in this research is descriptive analytic research with cross sectional approach, the total sample were 40 people were taken by purposive sampling technique. The data were collected using questionnaires intervention of parents and the impact of hospitalization compiled by Abdulbaki (2011) and later modified by the researcher, then re-tested for validity and reliability. The study was conducted early August until the end of October 2015. Result:The results of the analysis using Chi Square Test showed statistically significant correlation between the participation of parents with the impact of hospitalization on preschoolers with value 0:02 p values (p <0.05). This study founded 62.5% the intervention of parents was good and 60% of hospitalization impact on preschoolers was light. Conclusion:This study provides information that parents need to enhance their intervention of parents in caring for preschool children in order to minimize the impact of hospitalization on children.